AN ANALYSIS OF FIGURATIVE LANGUAGE USED IN WESTLIFE’S SELECTED SONGS - Abdul Muhid Murtadho; Amelia Amelia (STIBA IEC JAKARTA, 2022)
The purposes of this study are: (1) To find out the figurative language used in Westlife’s selected songs (2) To know the general meaning of lyrics on the Westlife’s selected songs. In analyzing of figurative language used in Westlife’s selected songs lyrics, the writer using qualitative research methodology, the data is taken from several books and internet as well as. Based on research finding, the general meaning contained in Westlife''s selected songs lyric indirectly deliver to the listeners through the lyrics they wrote.The lyrics try to tell about human social life which contains happiness, sadness, loneliness and others. The writer could identified that most of figurative language which used in Westlife’s selected songs lyric is “Hyperbole”. The writer got the data from the table. Hyperbole has a great exaggeration used to emphasize a point.